The domestic analogy and world order proposals - Suganami, Hidemi (Cambridge studies in international relations, 1989)
How profitable is it for world order to transfer the legal and political principles, which sustain order within states to the domain of relations between states? This has been one of the central and most contentious questions in the study of international relations. The term 'domestic analogy' refers to the idea that inter-state relations are amenable to the same type of institutional control as the relations of individuals and groups within states. In this study Dr Suganami discusses the role the domestic analogy has played in proposals about world order, peace, justice and welfare in the period since 1814. As well as analysing the ideas of major writers on international law and relations, Hidemi Suganami examines the creation of the League of Nations, the United Nations and its agencies, and the European Community - all of which have sprung from the domestic analogy. The Domestic Analogy and World Order Proposals makes an important contribution to the history of ideas about world order, exploring how this particular mode of reasoning about international relations has evolved against changing historical backgrounds